The Study of Values and Morals upon Tere Liye's Novel Moga Bunda Sayang Alloh - Nurul Fauziah, Sholikhatun (International Proceedings of Nusantara Raya, 2022)
Moga Bunda Disayang Alloh is a novel written by Tere Liye that recounts the narrative of the suffering of a family and a child who is blind, deaf, and mute. There are numerous principles and values that we might adopt in life. A commensurate desire will result from laborious effort, perseverance, and optimism. This research intends to explicate the principles and values of life in Moga Bunda Disayang Alloh Written By Tere Liye. This research's problem statement considers how the novel Moga Bunda Disayang Alloh Karya Tere Liye presents its values and morals. The technique employed is descriptive. An objective research methodology was adopted in this research. Analysis of the data with intrinsic analysis, the novel Moga Bunda Disayang Alloh is the source of data for this evaluation, including narrative, topic, message of the story, characters, characterizations, and point of view data extracted from the text. The research results from the novel Moga Bunda Disayang Alloh essential part interesting morals and values. Patience, regret, enthusiasm, perseverance, hard effort, compassion, and sincerity are some of the values that can be gleaned from the novel. Regarding the moral element, being grateful, praying, being willing to sacrifice, accepting one's responsibilities, and providing assistance are all essential. The interesting aspect of hardship is the happiness it produces. That at the conclusion of the story, despite his difficulties, the child is able to speak beautifully to his mother.